Selection for anthelmintic resistant Teladorsagia circumcincta in pre-weaned lambs by treating their dams with long-acting moxidectin injection. Issue 3 (December 2015) - Leathwick, D.M.; Miller, C.M.; Fraser, K.
Abstract: Administration of long-acting anthelmintics to pregnant ewes prior to lambing is a common practice in New Zealand. Today, most of these products contain macrocyclic lactone (ML) actives, which because of their lipophilic nature, are detectable in the milk of treated animals and in the plasma of their suckling offspring. This study was conducted to confirm the transfer of ML actives to lambs in the ewe's milk, and to assess whether this could result in selection for ML resistant nematodes in the lamb. Ninety, twin bearing Romney ewes were treated before lambing with a long-acting injectable formulation of moxidectin, a 100-day controlled release capsule (CRC) containing abamectin and albendazole, or remained untreated. After lambing, seven ewes from each treatment group were selected for uniformity of lambing date and, along with their twin lambs, relocated indoors. At intervals, all ewes and lambs were bled, and samples of ewe's milk were collected, for determination of drug concentrations. Commencing 4 weeks after birth all lambs were dosed weekly with 250 infective larvae (L3) of either an ML-susceptible or –resistant isolate of Teladorsagia circumcinta . At 12 weeks of age all lambs were slaughtered and their abomasa recovered for worm counts. Moxidectin was detected in the plasma of moxidectin-treated ewes until about 50 days after treatment and in their lambs until about day 60. Abamectin was detected in the plasma of CRC-treated ewes until the last sample on day 80 and in the plasma of their lambs until about day 60. Both actives were detectable in milk of treated ewes until day 80 after treatment. Establishment of resistant L3 was not different between the treatment groups but treatment of ewes with moxidectin reduced establishment of susceptible L3 by 70%, confirming the potential of drug transfer in milk to screen for ML-resistance in the suckling lamb. Graphical abstract: Highlights: Long-acting anthelmintics were administered to pregnant ewes. Moxidectin and abamectin were detected in ewe's milk for >60 days. Moxidectin and abamectin were detected in plasma of lambs for >60 days. Abamectin treatment had not effect on establishment of larvae in the lambs. Moxidectin treatment reduced establishment of susceptible, but not resistant larvae.